A review of pyrolysis technologies and feedstock: A blending approach for plastic and biomass towards optimum biochar yield. (October 2022) - Al-Rumaihi, Aisha; Shahbaz, Muhammad; Mckay, Gordon; Mackey, Hamish; Al-Ansari, Tareq
Abstract: The efficient and sustainable disposal or value addition of waste plastic has of major importance. Recent studies on the char produced via pyrolysis have demonstrated that it is a valuable additive with multiple applications ranging from soil and water amendment, improving agricultural yield, supercapacitors, fuel cells, and in support/catalysts, sustainable chemistry, and carbon sequestration. Thus, it is essential to ensure the quality and efficacy of biochar produced from any combination of feedstock and process to ensure maximum benefits. However, very few studies have focussed on techniques or process parameters to optimize biochar yield. This study aims to review pyrolysis techniques, reactor types, and pyrolysis parameters to identify the process parameters that could enhance the generation of biochar from co-pyrolysis of plastic and biomass feedstock. This review discusses biochar production techniques, the mechanism of pyrolysis technology, pyrolysis types, and the reactor types. This is followed by a review of the factors that can be used to optimize biochar production. Accordingly, the review identified temperature, heating rate, reactor bed height and type, residence time, pressure, feedstock type and blending ratio of feedstock as the determinants that had the highest influence on the yield, stability, and carbon content of biochar. Most importantly, the technology readiness level (TRL) of biomass pyrolysis, plastic pyrolysis and co-pyrolysis of biomass and plastic is discussed. The review necessitates further studies on these parameters to ascertain the accuracy of optimization that can be achieved by configuring pyrolysis processes to biochar production. Highlights: Co-pyrolysis of plastic, biomass and their blends are reviewed. Pyrolysis type, mechanisms, and reactor types are critically reviewed. Process parameters for optimum biochar yield production is discussed. Technical maturity of the pyrolysis process, challenges, and research gaps are discussed.